Sociodemografic and Clinical Characteristics of Suicidal Cases who Attempted to Emergency Services in Ankara - Selma ERCAN; Mustafa AKSOY; Abdussamed YALCIN; A. Cigdem SIMSEK; S. Rahmi ACAR; Tulay ERCIN SAHIN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of the study is to determine the sociodemografic and clinical characteristics of suicide attempted cases who were admitted to the emergency departments of the hospitals in the first six months of 2010 in Ankara. Methods: Data were obtained by examining the suicide attempted registration forms that were filled out in the emergency services of hospitals working for the Ministry of Health retrospectively. Results: The incidence of suicide attempts in women (76.5%) is higher than men (23.5%). Suicide attempts are high in 15-24 group of age (59.3 %). The rate of suicide attempts is high in patients who were single (57.9 %) and students who were in education level of secondary (44.6 %) and high school (40.2 %). The most common hospitals that were applied are Ankara Training and Researsch Hospital (29.8%) and Kecioren Training and Research Hospital (12.4%). Also Mamak (19.7%) and Kecioren (17.2%) are towns that cases were seen mostly. The most applied method of suicide attempted is the usage of drugs and toxic substances with the 96.2%. The increment ratio of the suicide attempts is seen paticularly from January to June. Family (16.0%) and psychiatric disorder (15.2%) are mainly stressors leading to suicide attempted. Discussion: All attempted suicide patients who applied to Emergency Department should be directed to Crisis Intervention Unit immediately and following-up the cases with psychiatric consultation must become obligatory as well as medical treatments. The findings have been discussed with the literature. [JCBPR 2016; 5(1.000): 5-12]